Chromosome‐level assembly of Culex pipiens molestus and improved reference genome of Culex pipiens pallens (Culicidae, Diptera). (18th September 2022) - Liu, Wenjuan; Cheng, Peng; An, Sha; Zhang, Kexin; Gong, Maoqing; Zhang, Zhong; Zhang, Ruiling
Abstract: Culex pipiens molestus and Culex pipiens pallens are two distinct bioforms in the Culex pipiens complex that are important vectors of several pathogens and are widely distributed around the world. In the current study, we present a high‐quality chromosome‐level genome of Cx . pipiens f. molestus and describe the genetic characteristics of this genome. The assembly genome was 559.749 Mb with contig and scaffold N50 values of 200.952 Mb and 0.370 Mb, and more than 94.78% of the assembled bases were located on 3 chromosomes. A total of 19, 399 protein‐coding genes were predicted. Many gene families were expanded in the genome of Cx . pipiens f. molestus, particularly those of the chemosensory protein (CSP) and gustatory receptor (GR) gene families. In addition, utilizing Hi‐C data, we improved the previously assembled draft genome of Cx . pipiens f. pallens, with scaffold N50 of 186.195 Mb and contig N50 of 0.749 Mb, and more than 97.02% of the assembled bases were located on three chromosomes. This reference genome provides a foundation for genome‐based investigations of the unique ecological and evolutionary characteristics of Cx . pipiens f. molestus, and the findings in this study will help to elucidate the mechanisms involved in species divergence in the Culex pipiens complex.